In vivo assessment of macula in eyes of healthy children 8 to 16 years old using optical coherence tomography angiography - Zhengwei Zhang (Nature Portfolio, 2017)
Abstract The purpose of the present study was to investigate the vascular flow density (VD) of macular superficial (SCP), deep capillary plexus (DCP), and choriocapillaris and the size of the foveal avascular zone (FAZ) area in healthy children using optical coherence tomography angiography (OCTA). The potential associations of age, sex, intraocular pressure, body mass index, spherical equivalent, and axial length with OCTA parameters were also investigated. A total of 75 eyes from 75 healthy children were included for analysis, with the mean age 11.51 ± 1.91 years (range, 8–16 years). At the level of the SCP, mean VD and mean FAZ area were, respectively, 54.29 ± 2.25% and 0.290 ± 0.109 mm2. At the level of the DCP and choriocapillaris, mean VD were 60.19 ± 1.76% and 66.58 ± 1.33%, respectively. After adjustment on the signal strength index, there was no significant correlation between age and all OCTA parameters. Intra-observer repeatability was 0.91, 0.82, and 0.88 in the SCP, DCP and choriocapillaris, respectively. In healthy eyes of children, only sex has a significant influence on the FAZ area. OCTA may provide a noninvasive and reliable approach for evaluating macular perfusion in children, although sex-related variations should be considered.